Skip to main content

Binomial Theorem

(p+q)n=โˆ‘k=0n(nk)pkqnโˆ’k(p + q)^n = \sum\limits_{k=0}^n {n \choose k} p^k q^{n-k}

โˆ‘j=1โˆžaj=a1โˆ’a,โˆฃaโˆฃ<1\sum\limits_{j=1}^{\infty} a^j = {a \over {1-a}}, |a| < 1

SN=โˆ‘j=1NajS_N = \sum\limits_{j=1}^N a^j

SN=a+a2+โ‹ฏ+aNS_N = a + a^2 + \cdots + a^N โ€” โ‘ 

aSN=a2+โ‹ฏaN+1aS_N = a^2 + \cdots a^{N+1} โ€” โ‘ก

If we subtract โ‘ก from โ‘ , we get

SN=aโˆ’an+11โˆ’aS_N = {{a - a^{n+1}} \over {1-a}}

โˆ‘k=1โˆžkak=a(1โˆ’a)2\sum\limits_{k=1}^{\infty} k a^k = {a \over (1-a)^2}

limโกnโ†’โˆž(1+xn)n=ex\lim\limits_{n \to \infty} ({1 + x \over n})^n = e^x

Number of OutcomesWith ReplacementWithout Replacements
2Binomial (different when until*\text{until}^\text{*}...)Hypergeometric
โ‰ฅ\geq 3MultinomialMultivariate Hypergeometric

until*\text{until}^\text{*}โ€‹

  • 1st1^{\text{st}} success โ†’ geometric
  • rthr^{\text{th}} success โ†’ negative binomial

In Probability,

(p+q)n=โˆ‘k=0n(nk)pkqnโˆ’k(p+q)^n = \sum\limits_{k=0}^n {n \choose k} p^k q^{n-k}

Proofโ€‹

Base caseโ€‹

Let n=1n=1. Then

โˆ‘k=01(1k)pkqnโˆ’k=(10)p0q1+(11)p1q0\sum\limits_{k=0}^1 {1 \choose k }p^k q^{n-k} = {1 \choose 0} p^0 q^1 + {1 \choose 1} p^1 q^0

Induction Hypothesisโ€‹

Assume that (p+q)m=โˆ‘k=0m(1m)pkqmโˆ’k(p+q)^m = \sum\limits_{k=0}^m {1 \choose m }p^k q^{m-k}. Let n=m+1n = m+1. Then

(p+q)m+1=(p+q)(p+q)m=(p+q)โˆ‘k=0m(1m)pkqmโˆ’k(p+q)^{m+1} = (p+q) (p+q)^m = (p+q) \sum\limits_{k=0}^m {1 \choose m }p^k q^{m-k} pโˆ‘k=0m(mk)pkqmโˆ’k+qโˆ‘k=0m(mk)pkqmโˆ’kp \sum\limits_{k=0}^m {m \choose k}p^k q^{m-k} + q \sum\limits_{k=0}^m {m \choose k}p^k q^{m-k} โˆ‘k=0m(mk)pk+1qmโˆ’k+โˆ‘k=0m(mk)pkqmโˆ’k+1\sum\limits_{k=0}^m {m \choose k}p^{k+1} q^{m-k} + \sum\limits_{k=0}^m {m \choose k}p^k q^{m-k+1}

Let j=k+1j=k+1 and k=jโˆ’1k=j-1 for the first and j=kj=k for the second sum. Then,

โˆ‘j=1j=m+1(mjโˆ’1)pjqm+1โˆ’j+โˆ‘j=0j=m(mj)pjqmโˆ’j+1\sum\limits_{j=1}^{j=m+1} {m \choose {j-1}}p^{j} q^{m + 1 - j} + \sum\limits_{j=0}^{j=m} {m \choose j}p^j q^{m-j+1}